IMPLEMENTASI METODE SAW DALAM PENDUKUNG KEPUTUSAN PEMBERIAN REWARD BAGI TENAGA PENGAJAR - Handayani, Masitah; Sibuea, Mustika Fitri Larasati; Sundari, Sundari (Smart Education, 2025)
Abstract: Rewarding is an important strategy in increasing individual motivation and performance, both in educational environments, companies, and other organizations. However, the process of selecting reward recipients is often done subjectively, which can lead to dissatisfaction and potential injustice. Therefore, an objective and measurable method is needed to determine reward recipients in a more transparent and fair manner. One of the decision-making methods that can be applied in this process is the Simple Additive Weighting (SAW) method. The SAW method is known as a simple and effective method in assessing alternatives based on predetermined criteria. With clear criteria weights and values, this method is able to provide more objective results in the reward recipient selection process. Rewarding based on the SAW method aims to increase objectivity and transparency in the selection of reward recipients because it has assessment indicators for each criterion in each alternative involved. There are nine classes of teaching staff who are assessed using the SAW Method with four assessment criteria in awarding rewards, namely Last Education, Length of Service, Discipline and Teaching Methods. Based on these calculations, the alternative that is entitled to receive a reward is A01 with the highest Vi value of 0.95 Keywords: SAW Method, Reward, Instructor Abstrak: Pemberian reward merupakan salah satu strategi penting dalam meningkatkan motivasi dan kinerja individu, baik dalam lingkungan pendidikan, perusahaan, maupun organisasi lainnya. Namun, proses pemilihan penerima reward sering kali dilakukan secara subjektif, sehingga dapat menimbulkan ketidakpuasan dan potensi ketidakadilan. Oleh karena itu, diperlukan metode yang objektif dan terukur untuk menentukan penerima reward secara lebih transparan dan adil. Salah satu metode pengambilan keputusan yang dapat diterapkan dalam proses ini adalah metode Simple Additive Weighting (SAW). Metode SAW dikenal sebagai metode yang sederhana dan efektif dalam menilai alternatif berdasarkan kriteria yang telah ditentukan. Dengan bobot dan nilai kriteria yang jelas, metode ini mampu memberikan hasil yang lebih objektif dalam proses seleksi penerima reward. Pemberian reward berbasis metode SAW bertujuan untuk meningkatkan objektivitas dan transparansi dalam pemilihan penerima reward karena memiliki indikator penilaian untuk setiap kriteria pada masing-masing alternative yang terlibat. Ada Sembilan beklas orang tenaga pengajar yang dinilai menggunakan Metode SAW dengan empat kriteria penilaian dalam pemberian reward yaitu Pendidikan Terkahir, Lama Bekerja, Kedisiplinan dan Metode Pengajaran. Berdasarkan perhitungan tersebut alternative yang berhak mendapatkan reward adalah adalah A01 dengan nilai Vi tertinggi adalah 0,95. Kata kunci: Metode SAW, Reward, Tenaga Pengajar